Design and performance testing of a 2.29-GB - Verbauwhede, I. (IEEE Journal of solid state circuits)
This contribution describes the design and performance testing of an Advanced Encryption Standard (AES) compliant encryption chip that delivers 2.29 GB/s of encryption throughput at 56 mW of power consumption in a 0.18-μm CMOS standard cell technology. This integrated circuit implements the Rijndael encryption algorithm, at any combination of block lengths (128, 192, or 25 bits) and key lengths (128, 192, or 256 bits). We present the chip architecture and discuss the design optimizations. We also present measurement results that were obtained from a set of 14 test samples of this chip.